The protective role of melatonin in chemotherapy‐induced nephrotoxicity: a review of non-clinical studies. (2nd September 2018) - Haghi-Aminjan, Hamed; Farhood, Bagher; Rahimifard, Mahban; Didari, Tina; Baeeri, Maryam; Hassani, Shokoufeh; Hosseini, Rohollah; Abdollahi, Mohammad
BSTRACT: Introduction : The aim of this study was to investigate the potential role of melatonin in the prevention of chemotherapy-induced nephrotoxicity at the preclinical level. Areas to be covered : To illuminate the possible role of melatonin in preventing chemotherapy-related nephrotoxicity, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was followed. A comprehensive search strategy was developed to include PubMed, Web of Science, Scopus, and Embase electronic databases from their inception to May 2018. Based on a set of prespecified inclusion and exclusion criteria, 21 non-clinical articles were ultimately included in the study. Expert opinion : Our findings clearly demonstrate that melatonin has a protective role in the prevention of chemotherapy-induced nephrotoxicity which may be caused by different chemotherapy agents such as cyclophosphamide, cisplatin, doxorubicin, methotrexate, oxaliplatin, etoposide, and daunorubicin. On the basis of current review of non-clinical studies, this protective effect of melatonin is attributed to different mechanisms such as reduction of oxidative stress, apoptosis, and inflammation. The findings presented in this review are based on non-clinical studies and thus conducting appropriate clinical trials to evaluate the real effectiveness of the concurrent use of chemotherapy agents with melatonin in the cancer patients is necessary.